STUDY OF EXPOSITION PARAGRAPH DEVELOPMENT IN TARBIYAH AND TEACHER TRAINING FACULTY STUDENTS - Muhammad Hurmaini (JURNAL TARBIYAH, 2019)
This research was motivated by the low learning outcomes of developing the exposition paragraph of the students of the Tarbiyah and Teaching Faculty of UIN Sulthan Thaha Saifuddin Jambi. Students as prospective teachers had to be able to develop effective paragraphs than their students. This study aims to: describe the level of ability of students to develop exposition paragraphs, in terms of (1) aspects of paragraph cohesiveness, (2) aspects of the coherence of paragraphs, and (3) aspects of paragraph effectiveness. This research used a descriptive method. The selected sample was proportional randomly 34 pieces of exposition paragraphs, consisting of 1220 sentences written by 169 students from four study programs (Islamic Education, Madrasah Ibtidaiyah Teacher Education, Mathematics Education, and English Language Education). The method of data collection was in the form of essay tests. Data for each sentence and paragraph is analyzed and interpreted according to its classification by the process of sentences per sentence, and cards per card. After that tabulated then percentage.